Ethics and aesthetics in Jonas Lüscher's Barbarian spring - Hütter, Yvonne (Primerjalna književnost, 2017)
The article claims that Jonas Lüscher's first novel titled Barbarian Spring follows a twofold program: it is a book with a strong moral and political message, and at the same time it is challenging literature's possibility to incite action. Therefore, the book stands within the tradition of the Enlightenment when it comes to educating the reader, and in a larger sense, believing in the social value of Bildung; yet, it simultaneously shows the limits of the Enlightenment frame by decomposing the linkage between moral knowledge and actual behavior. To pursue this twofold goal, the book intertwines traditional aesthetic forms with modernist goals, and demonstrates in the end the limits of applicability and fertility of both approaches in today's context and when - as the text suggests - consequentialist categories are applied. The text diagnoses the malfunctioning of the syncretism of Capitalism, Christianity, and the Enlightenment not only when it comes to issuing rules for moral behavior, but also when it comes to giving meaning to experience. Following this second possible purpose of literature - sense-making - the book examines literature's therapeutic possibilities, when therapy means the integration in or the creation of a coherent interpretational scheme.
Keywords: literature and ethics; Lüscher, Jonas, 1976--; "Frühlung der Barbaren"; Swiss literature; literatura in etika; ethics and aesthetics; didactic function; švicarska književnost; therapeutic function; etika in estetika; social engagement; didaktičnost; terapevtskost; družbeni angažma